2016
DOI: 10.17058/cinergis.v18i1.8076
|View full text |Cite
|
Sign up to set email alerts
|

Desafios dos alunos com deficiência visual no ensino superior: um relato de experiência

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4. RESUMOO desenvolvimento histórico da Educação Especial e Inclusiva no Brasil é repleto de desafios e contradições entre a legislação, recursos e execução. Objetivo: investigar as dificuldades que uma ex-aluna, portadora de deficiência visual grave vivenciou durante a graduação em uma instituição de ensino superior pública. Método: trata-se de um estudo de caso desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…In order to overcome these difficulties and obstacles, several studies reported that self-esteem and social support are crucial. The academic achievement of students with disabilities is further attributed to individual effort and to the social support the students received (Alexandrino et al, 2016).…”
Section: Resilience For Academic Successmentioning
confidence: 99%
“…In order to overcome these difficulties and obstacles, several studies reported that self-esteem and social support are crucial. The academic achievement of students with disabilities is further attributed to individual effort and to the social support the students received (Alexandrino et al, 2016).…”
Section: Resilience For Academic Successmentioning
confidence: 99%
“…Therefore, the main purpose of this study is to discuss the process of inclusion of students with visual impairment in higher education and the applicable pedagogical practices. The paper uses the works of Pieczkowski (2012), Almeida & Castro (2014), Alexandrino et al, (2016), among others as its theoretical basis. It could be noted that the shortage of skilled professionals, the lack of specific materials, the inadequacy of physical spaces and the pedagogical practices that are carried out in a complacent manner prevent the permanence and limit the quality of education for people with visual impairment in higher education.…”
Section: Visual Impairment In Higher Education: Inclusion and Pedagogmentioning
confidence: 99%
“…Así, el principal objetivo de este estudio es discutir el proceso de inclusión de los alumnos con discapacidad visual en la enseñanza superior y en las prácticas pedagógicas. De esta forma, el aporte teórico de este artículo se basa en Pieczkowski (2012), Castro y Almeida (2014), Alexandrino et al, (2016), entre otros. Se constató que la escasez de profesionales cualificados, la falta de materiales específicos, la inadecuación de los espacios físicos junto con las prácticas pedagógicas que se realizan de forma complaciente, impiden la permanencia y limitan la calidad de la educación de las personas con discapacidad visual en la enseñanza superior.…”
Section: Introductionunclassified
“…Inclusive education seeks to provide individuals with some type of disability with conditions to develop their potential. However, difficulties for inclusion remain, such as the lack of adequate materials for some classes (Alexandrino et al, 2017). Adaptation of methods and resources is a daily challenge for teachers in schools and universities, as is the reformulation of curricula to ensure effective learning for disabled students (Fossey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the main challenges faced by the visually impaired are: mobility within schools and/or universities, writing, reading, and socializing with other students and teachers (Alexandrino et al, 2017; Monson, 2015; Otyola et al, 2017). Among courses in the health area, one subject that is a pillar for learning others is human anatomy (Johnston et al, 2016).…”
Section: Introductionmentioning
confidence: 99%